Filantropi Islam dalam Konteks Pembangunan Sumber Daya Manusia di Indonesia - Sulkifli, Sulkifli (IAIN Palopo, 2018)
Throughout the history of the pre-independence and post-independence Indonesia. The role of Islamic philanthropy has made important contributions in the welfare and empowerment of the public. Not in doubt that social and economic inequalities can be seen by the naked eye at the moment, nothing else due to swift currents of globalization and the development of the modern world that is unstoppable. This is reflected in the strong stance that is not altruistic individualism around. Islamic philanthropy comes with a carrying value of an underlying morality of the humanist spirit (human), that the human being with another human being the same, so it is important to eliminate all forms of discrimination, particularly to maintain the sustainability of human life on this earth. Social capital development in the era of globalization (globalization) is in need, given the free world economy (free market) is unbelievably intense competition and cruel. One of the foundations of social capital (human capital) is in addition to the knowledge and skills is the ability of people to make associations (associated) with each other. programs of BAZNAS with the distribution of zakat to the education sector is large enough, then the system development offered by the National Zakat Agency by allocating funds for charity, which reached 20.35 percent, or about 500 billion in the education sector, the other not only to achieve sustainable development which manifests itself with a system of human resource development through the provision of education funds to mustahik, either directly in the form of scholarships, research, support the renovation of schools, or the establishment of schools in the direct management BAZNAS. Modernization and globalization are progressing very significant, if not in conjunction with increased knowledge and the quality of education for the community itself, then a structured poverty will remain rampant.